IMPLEMENTASI PENGELOLAAN PAJAK RETRIBUSI PARKIR DI KOTA KENDARI - La Ode Mustafa; La Ode Muhammad Elwan (Universitas Halu Oleo, 2018)
The purpose of this study was to determine the management of parking levy taxes and efforts made by Kendari City government in optimizing the receipt of parking tax/retribution in Kendari City.The research method used is a qualitative research method with a descriptive analysis approach, data collection using interview, observation and documentation techniques. The data analysis technique used by the author is a qualitative data analysis technique that is by searching and compiling systematically from the results of interviews, observation and documentation then selecting the data needed and making conclusions that are easy to understand.Based on the results of the study, the management of parking fees that have been carried out so far has been quite good, can be seen from the percentage between the target and the realization of parking retribution from 2016-2018 experiencing fluctuations and in 2017 did not reach the target set, and the last 3 (three) years this contribution of parking fees to local original income is very small. This is because there are still many obstacles experienced by the Regional Tax and Retribution Management Agency in Kendari in managing parking fees. In the planning process has been going well can be seen in determining the target parking retribution per year which always refers to the results of the evaluation of the achievement of targets in the previous year and see the potential in the field. Organizing is still not effective, it can be seen from the standard of work of the parking fees officers still experiencing obstacles in the number of personnel. From the implementation efforts, it is still not effective in collecting parking taxes, such as the provision of parking permits, there are still some who do the installation without making prior permission and lack of awareness of the taxpayer about the importance of paying taxes which is the foundation for Kendari City Development. Only the supervision indicators carried out by superiors to subordinates are effective, such as monitoring carried out to evaluate the work is maximized, so as not to provide opportunities for individuals in the field to commit fraud. But supervision of the community is still not effective because there are still many illegal parking lots without having installation permits.